Book Reviews (The Muslim world, 1962)
Book reviewed in this article: British Interests in Palestine, 1800-1901. By A. L. Tibawi. Fusūl al-Madan? (Aphorisms of the Statesman, of al-Fārāb?). By D. M. Dunlop. Philosophical Activity in Pakistan 1947-1961. Special Supplement, International Philosophical Quarterly. By Richard V. De Smet. Islamische Mystiker By Tor Andrae; German translation by Helmart Kanus Credé. Dust in the Lion's Paw By Freya Stark. Avicenna and the Visionary Recital By Henry Corbin. Translated from the French by Willard R. Trask. Türkiyenin Siyasî Hayatinda Batililasma Hareketleri By Tarik Z. Tunaya. The Poetry and Prophecy of the Old Testament. A recording by Theodore Bikel. Symphonic setting composed and conducted by Don Seltzer.